Tuberculosis caused by Mycobacterium bovis infection in a donkey. (14th October 2016) - Bryan, J.; den Boon, P.; McGuirk, J.; Madigan, G.; Skuce, R.; Fogarty, U.
Summary: Mycobacterial infections are rare in equines. Mycobacterium bovis ( M .  bovis ) is an important zoonotic bacterial pathogen causing disease in a wide range of animal species and sporadically causes severe disseminated disease in horses. This report describes the clinical, gross post‐mortem examination and histopathological findings in a case of disseminated M. bovis infection in a donkey which to the authors' knowledge has not been previously documented in the scientific literature.